Tasawuf Transformatif di Indonesia - Nurul Anam; Sayyidah Syaikhotin; Hasyim Asy’ari (LPPM Institut Pesantren KH. Abdul Chalim, 2019)
In Islam there is an element of Sufism which is a very significant part of the existence of transformative Islam. From this transformative Islam the term transformative Sufism emerged. The transformative Sufism process will begin and center on marifah and tauhid. In the context of transformative Sufism, understanding of haqîqah starting from all the realities that bring people to the level of maahrifah must be realized / contextualized into the social-community context. Transformative Sufism is commonly found in Sufism assemblies in Indonesia, one of which is in the Maiyahan Mbah Nun Majlis (Ainun Nadjib) in Jogjakarta Province and Majlis Zikir Manakib Sheikh Abdul Qodir Al-Jailani KH. Ahmad Muzakki Syah in Jember Regency. These majlis events are interspersed with the planting of values ​​and the development of Islamic teachings and nationalities, so that finally the event in this assembly can be beneficial for changes for the community, especially the istiqamah pilgrims who attend this majlis. Both of these assemblies are based on Ahlussunnah Wal Jamaah Nahdlatul Ulama (NU). As is known, through the direction and guidance of KH. Hasyim Asy'ari and strengthened again by KH. Ahmad Siddiq and KH. Abdurrahman Wahid, NU institutionally acknowledged and established the Pancasila values ​​as the final basis for the Indonesian nation.